Vaping associated lung injury: A potentially life‐threatening epidemic in US youth. Issue 7 (6th April 2020) - Messina, Mark D.; Levin, Terry L.; Conrad, Laura A.; Bidiwala, Aneela
Abstract: Background: The Center for Disease Control (CDC) has identified a national outbreak in the United States of over 2600 cases of e‐cigarette or vaping product use‐associated lung injury (EVALI), including 60 deaths as of January 2020. We describe our experience in six adolescents. Material and Methods: We identified all pediatric patients diagnosed with EVALI by CDC guidelines over a 6‐month period at our health system. Clinical presentation, hospital course, and imaging were reviewed. Results: Six patients were identified (three males, three females; median age 18.5 years). Presenting symptoms varied, including constitutional, gastrointestinal, neurologic, and respiratory complaints with pulmonary symptomatology becoming the dominant feature of the illness. Three patients required intensive care unit‐level care, one of whom expired 36 days after presentation. Three had bronchoalveolar lavage, two with evidence of lipid‐laden macrophages. Four had pulmonary function testing with various results. Admission chest radiographs in all revealed bibasilar interstitial infiltrate which rapidly progressed. Five patients had computed tomography chest imaging demonstrating: confluent pulmonary infiltrates with subpleural sparing (n = 2), generalized ground‐glass opacities (n = 1), patchy ground‐glass opacities (n = 1) and a reticulonodular pattern (n = 1). Brain magnetic resonance imaging (MRI) obtained in two patients was normal in one and showed a focal signal abnormality in the corpus callosum in one. Conclusion: We describe the clinical course and radiologic findings of EVALI in our adolescent patients and present a new finding in the brain not yet described in the literature. Given the diversity of presenting symptoms, a high level of suspicion for EVALI is necessary for patients reporting vaping product use regardless of the presence of pulmonary complaints. Brain MRI should be strongly considered in patients with neurologic symptoms.